2018
DOI: 10.1371/journal.pone.0208449
|View full text |Cite
|
Sign up to set email alerts
|

Can patients be trained to expect shared decision making in clinical consultations? Feasibility study of a public library program to raise patient awareness

Abstract: IntroductionShared decision making (SDM) is a process whereby decisions are made together by patients and/or families and clinicians. Nevertheless, few patients are aware of its proven benefits. This study investigated the feasibility, acceptability and impact of an intervention to raise public awareness of SDM in public libraries.Materials and methodsA 1.5 hour interactive workshop to be presented in public libraries was co-designed with Quebec City public library network officials, a science communication sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Allowing service users to become subjective and reliable experts of their bodies, as well as active agents of their health, could ease the powerlessness and uncertainty that some service users experience towards improving their health. These findings are consistent with previous research on the need to improve health professionals-service users' communication [26][27][28][29]79], to foster two-way communication in clinical consultations [74], and to promote shareddecision making [20,30,31,[80][81][82][83] to improve health outcomes and reduce antibiotic prescribing [30,83]. Based on the concept of translation in sociology [84], Efforts to improve communication within healthcare should also consider the variance in the languages used by different agents in healthcare (e.g., service users and doctors) [79].…”
Section: Discussionsupporting
confidence: 90%
“…Allowing service users to become subjective and reliable experts of their bodies, as well as active agents of their health, could ease the powerlessness and uncertainty that some service users experience towards improving their health. These findings are consistent with previous research on the need to improve health professionals-service users' communication [26][27][28][29]79], to foster two-way communication in clinical consultations [74], and to promote shareddecision making [20,30,31,[80][81][82][83] to improve health outcomes and reduce antibiotic prescribing [30,83]. Based on the concept of translation in sociology [84], Efforts to improve communication within healthcare should also consider the variance in the languages used by different agents in healthcare (e.g., service users and doctors) [79].…”
Section: Discussionsupporting
confidence: 90%
“…75 It has been suggested that raising awareness of SDM through public campaigns may help prepare individuals seeking healthcare to ask for SDM during consultations and subsequently increase uptake. 76 HCPs should actively encourage pre-dialysis individuals with kidney failure to participate in SDM to ensure that treatment decisions are not made without the participation of the individual and/or their family/caregiver.…”
Section: Lack Of Hcp Engagementmentioning
confidence: 99%
“…Second, adopting an IKT approach improved our scaling up results in the following ways: (a) the involvement of library network stakeholders in identifying participating libraries could explain the high coverage of our scaling-up project; (b) prioritizing the public's perspective to identify the results to be disseminated, adopting a co-constructive approach to designing the workshops, and holding preparatory meetings to allow the workshop moderators to make the content of the message their own are all reasons that could explain our positive results in terms of acceptability and appropriateness among the public; These positive ndings are also consistent with those of our (non-IKT) pilot project. But interestingly, they also turned out to be of equal magnitude (19) despite the differences between the pilot project and the scaling up project. This last observation held also true for the increase in knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…These pilot workshops, designed to raise awareness of new knowledge in primary care research, took place across nine public libraries in Quebec City. We demonstrated evidence of their effectiveness through measuring the acquisition of knowledge among participants (19). We hypothesized that rst among the reasons for our pilot's positive results was the library setting.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation